Prevalence of Metabolic Syndrome in Patients with Psoriasis - Ilkin Zindancı; Ozlem Albayrak; Mukaddes Kavala; Emek Kocaturk; Burce Can; Sibel Sudogan; Melek Koç (The Scientific World Journal)
Background. Psoriasis is a chronic inflammatory skin disorder in which proinflammatory cytokines including IL-6 and TNF-α increase both locally and systematically. It is thought that chronic inflammation results in metabolic diseases and proinflammatory cytokines give rise to the development of atherogenesis, peripheral insulin resistance, hypertension, and type 2 diabetes. Our aim was to investigate the prevalence of metabolic syndrome in patients with psoriasis vulgaris. Methods. Study consisted of 115 plaque-type psoriasis patients and 140 healthy individuals. Data including body weight, height, waist circumference, body-mass index, and arterial blood pressure were collected. Fasting blood glucose, triglyceride, and HDL levels were determined. International Diabetes Federation Criteria for Metabolic Syndrome and Insulin Resistance were used for evaluating patients with metabolic syndrome and diabetes. Results. Compared to the control group, metabolic syndrome, diabetes mellitus, and hypertension were found to be higher in psoriasis patients. Metabolic syndrome was increased by 3-folds in psoriasis patients and was more prevalent in women than in men. It was determined that the prevalence of metabolic syndrome was higher in psoriasis patients after the age of 40. Metabolic syndrome was not related to smoking, severity of psoriasis, and duration of disease. Conclusions. Our findings suggest that psoriasis preconditions occurrence of a group of diseases such as diabetes mellitus, hypertension, and metabolic syndrome. For this reason, patients with psoriasis should be treated early and they should be followed with respect to metabolic diseases.